Improvement of Forecating and Inventory Control For Optimizing Inventory at PT United Tractors Site Muara Tiga Besar - Muhammad Ridho Fabio; Aditya T. Pratama; Gembong Baskoro (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2025)
PT United Tractors, Muara Tiga Besar site, is one of the company’s sites in Indonesia, responsible for accurately meeting customer demands in terms of timeliness, quantity, and quality. Ineffective and inefficient inventory management leads to idle capital and increased inventory costs, such as storage expenses and other inventory-related risks. Currently, PT United Tractors Muara Tiga Besar site has not yet optimized its inventory management, as evidenced by the Days of Inventory (DOI) performance in 2024 showing an upward trend, with the performance in May 2024 reaching 81.9 days. Therefore, this study aims to improve the DOI performance to meet the established targets. The root cause of the problem was identified using the 5 Why Analysis method, followed by generating ideas and solutions for improvement. The chosen solutions include forecasting using the Simple Moving Average method and inventory control through the Periodic Review and Continuous Review Systems. The research results indicate that forecasting with this purpose method effectively reduces DOI performance to 72 days, while inventory control using the Continuous Review System significantly reduces storage costs by 49%, achieving a more efficient outcome. Keywords — DMAIC, 5 Why Analysis, Forecasting, Simple Moving Average, Periodic Review System, Continuous Review System